The Development of Arrum Haji Products at Pegadaian Syariah: Empirical Evidence from The Sumenep Branch Office - Iqbal Rafiqi; Qanita Aulia Kharida; Maftuhatul Faizah; Moh. Jufriyadi Sholeh; Muhammad Nurul Yaqin (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to evaluate the business development and growth trajectory of the Arrum Haji product at the Pegadaian Syariah Sumenep Branch Office. Employing a qualitative research design, data were gathered through comprehensive observation, in-depth interviews, and meticulous documentation. The analytical framework involved data reduction, data display, and conclusion drawing, with methodological triangulation utilized to ensure data validity. The findings reveal a consistent upward trend in the overall performance of the Sumenep Branch from 2019 to 2023. Specifically, the customer base expanded from 46,633 to 48,092, while the annual turnover surged from IDR 523,037,920,000 to IDR 595,126,415,270, representing a significant 115% growth. Regarding the Arrum Haji product, the branch successfully acquired 50 customers during the same period. Despite the steady progress, the penetration rate for Arrum Haji remains relatively modest. This limited adoption is primarily attributed to the product’s nascent stage in the market. This research provides strategic insights into the early-stage adoption of Sharia-compliant pilgrimage financing within the pawnshop industry.